"I Feel Sad": The Cultural Politics of White Emotions in Pre-Service Teachers’ Response to Literature - Bauck, Kristin (Educational (Re)naissance, 2024)
This paper details a critical ethnography I conducted in my own classroom—an undergraduate children’s literature course for pre-service elementary educators—in which I analyze White students’ emotional responses to multicultural children’s literature through the lens of a cultural politics of emotion (Ahmed, 2015; Zembylas, 2008). In my paper I use critical Whiteness studies and critical emotion studies to analyze the effects of these emotional responses, complicating the assumption that emotions are a bridge to empath and exploring how White emotional performativity often serves to deflect from authentic critical discourse, reinforcing White supremacy in educational spaces. I look reflexively at my own pedagogy as a White educator, noticing the ways in which my failure to critically interrogate White emotions contributed to a classroom culture that valued majority voices over the voices of students of color. I conclude with the impacts of this study on my own commitments as a teacher-researcher.